Support or Suppress? Research on the Mechanism of Employee’s GNS on Innovation Performance: From the Perspective of Status Competition - Tang, Yuhong; Ding, Zhenkuo; Hu, Xiwu; Tao, Ran (Frontiers in Psychology, 2022)
The purpose of this paper is to investigate how supervisor’s mental state and behavior choice affect the relationship between employees’ strong growth need (GNS) and their innovation performance. Using 210 sets of supervisor-subordinate dyads data from two-wave survey, this research reveals that GNS has a significant positive effect on innovation performance, and leader–member exchange (LMX) mediates the effect of GNS on innovation performance. Supervisor perceived status threat moderates the relationship between GNS and LMX, such that this relationship gets weaker for supervisors with higher perceived status threat. Furthermore, supervisor perceived status threat moderates the relationship between GNS and innovation performance, such that this relationship becomes weaker for supervisors with higher perceived status threat. The study concludes with theoretical and practical implications, as well as future research avenues.